Efecto del método Dáder aplicado en pacientes mixtos del programa Control de Enfermería: Diabetes Mellitus - Hipertensión Arterial (Dm - Hta) del hospital II – Essalud Tarapoto - Castañeda Vásquez, Yajaira Daniela (2016)
The following research work was aimed to determine the effect of the Dader method applied in mixed patients of the Nursing Control program: Diabetes Mellitus - Arterial Hypertension (DM - HTA) of Tarapoto II - EsSalud Hospital. This is a descriptive-pre-experimental study, with quantitative, prospective, transversal cut approach. The sample was consisted of 37 patients chosen for convenience; also a form prepared by the researchers was used as data collecting instrument, which allowed the collection of data in the pre and posttest. The final results after the application of the Dader method show that of 151 problems found in three dimensions (Need, Efficiency and Security), 132 of them were solved representing 87%. Finally the hypothesis is accepted due to the fact that the effect of the Dader Method applied in Mixed Patients of the Program Control of Nursing: Diabetes Mellitus - Arterial Hypertension (DM - HTA) of the Tarapoto II - EsSalud Hospital is significant and positive